A Case Report on Ayurvedic Management of Perimenopausal Bleeding (International Journal of Ayurveda and Pharma Research, 2021)
Perimenopausal period is the transitional period where a woman passes from the reproductive to the non-reproductive stage. Abnormal uterine bleeding in the perimenopausal period accounts for 70% of all gynecological problems. Most of the abnormal uterine bleeding in this period is due to endometrial abnormalities. In Ayurveda the condition can be correlated to Asrigdhara. This is the case report of a 54 year aged lady who presented with complaints of excessive bleeding and frequent menstrual cycles since three months. Investigations were done to rule out malignancy. USG report showed endometrial hyperplasia of 17mm with bulky uterus. Pap smear and Colposcopy reports showed inflammatory and CIN I changes with HPV flat lesions respectively. Bleeding stopped after two weeks of internal medication. USG done after six months showed significant reduction in endometrial thickness. Pronounced changes were also seen in Pap smear and Colposcopy findings.